2020
DOI: 10.1089/bfm.2019.29144.psb
|View full text |Cite|
|
Sign up to set email alerts
|

Bedsharing and Breastfeeding: The Academy of Breastfeeding Medicine Protocol #6, Revision 2019

Abstract: A central goal of the Academy of Breastfeeding Medicine is the development of clinical protocols for managing common medical problems that may impact breastfeeding success. These protocols serve only as guidelines for the care of breastfeeding mothers and infants and do not delineate an exclusive course of treatment or serve as standards of medical care. Variations in treatment may be appropriate according to the needs of an individual patient. Purpose B edsharing promotes breastfeeding initiation, 1 duration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 103 publications
0
24
0
Order By: Relevance
“…The incidence of unintentional suffocation in children <1 year of age was high, and the reasons are as follows: it is mainly due to the imperfect physiological functions of newborns and infants and poor care by parents, which leads to asphyxia in bedding or improper feeding, and asphyxia caused by foreign bodies in the respiratory tract. 28 In China, children have the habit of sleeping in the same bed with their parents, where quilts and pillows cover the baby's mouth and nose or parents' arms and legs oppress the baby's respiratory tract at night, resulting in unintentional suffocation. 29 The Academy of Breastfeeding Medicine 30 and some studies 31 have shown that sharing a bed alone does not increase the risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of unintentional suffocation in children <1 year of age was high, and the reasons are as follows: it is mainly due to the imperfect physiological functions of newborns and infants and poor care by parents, which leads to asphyxia in bedding or improper feeding, and asphyxia caused by foreign bodies in the respiratory tract. 28 In China, children have the habit of sleeping in the same bed with their parents, where quilts and pillows cover the baby's mouth and nose or parents' arms and legs oppress the baby's respiratory tract at night, resulting in unintentional suffocation. 29 The Academy of Breastfeeding Medicine 30 and some studies 31 have shown that sharing a bed alone does not increase the risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Responding consistently, quickly and warmly to infant needs or distress is essential for a secure attachment (Canadian Paediatric Society, 2019). Skin‐to‐skin contact (Moore, Bergman, Anderson, & Medley, 2016) and proximity, especially at night‐time, facilitate breastfeeding duration and exclusivity (Blair et al, 2020; L. A. Smith et al, 2016). Keeping infants in the same room as the parents for at least 6 months, or ideally, until 1 year can prevent sudden infant death syndrome (SIDS) (American Academy of Pediatrics, 2020d).…”
Section: Shared Decision‐making Process For Infant Care and Feeding Dmentioning
confidence: 99%
“…Responding consistently, quickly and warmly to infant needs or distress is essential for a secure attachment (Canadian Paediatric Society, 2019). Skin-to-skin contact(Moore, Bergman, Anderson, & Medley, 2016) and proximity, especially at night-time, facilitate breastfeeding duration and exclusivity(Blair et al, 2020;L. A. Smith et al, 2016).…”
mentioning
confidence: 99%
“…There has been a very strong tendency for researchers to lump all infant deaths under the rubric of SIDS. This was exemplified by recent papers where all infant deaths in shared sleeping environments were called SIDS, including cases where the deaths occurred on the narrow, sloped and soft surfaces of a sofa/couch that was being shared with an adult [2][3][4]. The lack of acknowledgment that at least some of these cases must be due to suffocation is of concern.…”
mentioning
confidence: 99%
“…While it has been stated that the risk of accidental suffocation in bed sharing infants who are being breast fed is "extremely rare" in the absence of "hazardous circumstances" [4], it could be suggested that the very nature of this activity in bed is a potential hazard [14,15], particularly with recent increases in body mass index in many communities [16,17]. The reality is that any tired or intoxicated mother who is breastfeeding in bed is at risk of falling asleep and causing lethal obstruction of her infant's airway.…”
mentioning
confidence: 99%